2017
DOI: 10.1061/(asce)gt.1943-5606.0001768
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness of Soil–Geosynthetic Composite under Small Displacements: I. Model Development

Abstract: While significant emphasis has been placed on the quantification of soil-geosynthetic properties under failure conditions, studies of properties that are suitable for characterizing this interaction under serviceability conditions have been limited. Also, most geosynthetic properties are currently defined in isolation rather than under the confinement of soil. The purpose of this study is to develop a soil-geosynthetic interaction framework that, with a single and repeatable parameter, can capture the stiffnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Detailed analysis of the values for the calculated pavement elastic modules indicated that the pavement and the subsoil were of high rigidity, which is in agreement with the assumptions made by Zornberg et al [39] and Sudarsanan, et al [40]. At the same time, in the section of increased deflections (i.e., from 323 + 800 km to 324 + 00 km-southern section), the value of modules was reduced.…”
Section: Results and Discussion On The Research Outputssupporting
confidence: 87%
“…Detailed analysis of the values for the calculated pavement elastic modules indicated that the pavement and the subsoil were of high rigidity, which is in agreement with the assumptions made by Zornberg et al [39] and Sudarsanan, et al [40]. At the same time, in the section of increased deflections (i.e., from 323 + 800 km to 324 + 00 km-southern section), the value of modules was reduced.…”
Section: Results and Discussion On The Research Outputssupporting
confidence: 87%
“…Fannin and Raju (1993) used strain gages to check the longitudinal deformation along the geosynthetic. Authors such as Palmeira (2009), Ferreira and Zornberg (2015), Bathurst and Ezzein (2017), and Zornberg et al (2017) also presented different proposals and more complex approximations for the calculation of the confined stiffness of the geosynthetics using pullout tests. These approximations appear to be significantly better for the calculation of confined deformation of the geotextile than the calculation of the deformations directly by the displacement between two consecutive points.…”
Section: Jc =mentioning
confidence: 99%
“…Consequently, neither failure strain nor strength were considered when a suitable model geogrid was selected. Zornberg et al (2017) showed using a parameter defined as the stiffness of the soil-geosynthetic composite that both confined stiffness and interface shear strength (a function of bond) are required to describe the behaviour of reinforced granular materials at small strain. Consequently, the remaining two fundamental geogrid properties, stiffness and bond, were of importance when selecting a model geogrid for centrifuge testing.…”
Section: Materials Usedmentioning
confidence: 99%